2023
DOI: 10.1177/00219983231204407
|View full text |Cite
|
Sign up to set email alerts
|

In situ and offline mapping analyses of fatigue behavior in carbon-fiber-reinforced polymers by small- and wide-angle X-ray scattering

Masatoshi Todaka,
Kakeru Obayashi,
Ryosuke Kawatoko
et al.

Abstract: Although carbon-fiber-reinforced polymers (CFRPs) have excellent mechanical properties and are considered sustainable, an improved understanding of the fatigue behavior of these materials is crucial for expanding their application scope. The aim of this study is to clarify the fatigue mechanism of CFRPs using in situ and offline mapping by small-angle/wide-angle X-ray scattering (SAXS/WAXS) measurements. The resulting findings provide information about the interface between the carbon fibers (CFs) and epoxy ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…Also, X-ray spectroscopy is useful for an opaque sample. Synchrotron radiation X-ray can be used to evaluate not only CFs but also the orientation of the polymer chains and craze formation during uniaxial elongation. Furthermore, when the microbeam X-ray is used for this measurement, information on the interface between (CF/matrix polymer) may be obtained by mapping. Schneider et al reported spatial distribution of failed interface and voids near the broken fiber edges in the epoxy matrix near the glass fibers in a stretched sample using microbeam small-angle X-ray scattering (SAXS) . Takahashi et al observed localized debonding and voiding in a single-CF epoxy resin using synchrotron radiation X-ray computed tomography upon applying stress or cyclic stress to the sample .…”
Section: Introductionmentioning
confidence: 99%
“…Also, X-ray spectroscopy is useful for an opaque sample. Synchrotron radiation X-ray can be used to evaluate not only CFs but also the orientation of the polymer chains and craze formation during uniaxial elongation. Furthermore, when the microbeam X-ray is used for this measurement, information on the interface between (CF/matrix polymer) may be obtained by mapping. Schneider et al reported spatial distribution of failed interface and voids near the broken fiber edges in the epoxy matrix near the glass fibers in a stretched sample using microbeam small-angle X-ray scattering (SAXS) . Takahashi et al observed localized debonding and voiding in a single-CF epoxy resin using synchrotron radiation X-ray computed tomography upon applying stress or cyclic stress to the sample .…”
Section: Introductionmentioning
confidence: 99%